STRATEGI PERUSAHAAN ASURANSI PRUDENTIAL DALAM MENINGKATKAN NASABAH DAN MINAT BERASURANSI MASYARAKAT MUSLIM INDONESIA - Yuni Komariah; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Indonesia is a country with muslim poeple as majority, and Prudential Insurence company sees it as an opportunity to fullfil muslim people’s need with the insurence based on sharia. That is why Prudential Insurence company has strategy to launch sharia insurence product and it is called Prudential Unit Link Sharia Account and also increasing the ability of agents as negotiator for marketing the sharia product.This research aims to determine about the strategy of Prudential Insurence company to increase customer and gain muslim people’s interest on insurence in Indonesia. Prudential company comes from United Kingdom and currently become the biggest and the best insurence company in Indonesia.This reasearch is based on librarian research like book, relevant journal, newspaper and internet. In this research, the writer uses qualitative and quantitative research method. Using a level analysis of group, the perspective uses is liberal perspective to understanding the strategies use by Prudential Insurance company.Keyword: Prudential, Insurence, Muslim Indonesia, Sharia.